Study the effect of seed extracts of pumpkin (cucurbita maxima) in treatment of experimentally infected with hydatidosis disease for E.granulosus in laboratory rats - Al-Mayali, Hadi.M.; Anah, Saad.A. (Al-Qadisiyah Journal of Pure Science, 2017)
The present study amied to determine the effect extracts seed of pumpkin (cucurbita maxima) for depression of the protoscolices of Echinococcus granulosus in vitro,and determination of the therapeutic doses of these extracts for treatment of the secondary hydatid cysts in experimentally infected rats with negative cntrol group . In vitro Protoscolices were treated with concentrations (30,40,50,60)mg/ml of three extracts(cold water,hot water and alcoholic extract) at different time periods (1,6,12,24) hr after treatment,the result showed that cold water extract 60mg/ml was the most efficient to kill the protoscolices then hot water and lastiy alcoholic extract. Median lethal dose (LD50) estimated for (cold water,hot water and alcoholic extracts),then estimated therapeutic doses were calculated and these represented by (51.6,54.2,56.3)g/kg respectively. Rats are inoculated with (2000) protoscolices per rat ,and treated with the therapeutic doses of extracts. After three month of inoculations and on the basis of therapeutic efficieny of extracts,resuts showed that the cold water extract is more efficient for reduction of secondary hydatid cysts .